Pengaruh Digital Marketing, Brand Ambasssador Exo, Dan Brand Image Terhadap Minat Beli Scarlett Whitening (Studi Kasus Pada Penggemar Exo Di Surakarta) - Hana Yulita Safitri; Kusdiyanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of digital marketing, EXO brand ambassador, and brand image on purchase intention of Scarlett Whitening products among EXO fans in Surakarta. A quantitative approach was used by collecting data through closed questionnaires distributed to 100 respondents selected using purposive sampling. The variables studied include digital marketing, brand ambassador, and brand image, measured with relevant indicators. The results show that digital marketing, EXO brand ambassador, and brand image have a significant effect on purchase intention. Effective digital marketing through social media and creative promotions can attract consumer interest, while EXO’s involvement as a brand ambassador builds an emotional connection with fans, strengthening positive perceptions of the product. A positive brand image also plays an important role in building trust and increasing purchase intention. This study provides practical implications for companies in developing digital marketing strategies and selecting the right brand ambassador.